2022
DOI: 10.1177/09544089221134394
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficiency of perovskite solar cells using Cs4CuSb2Cl12 quantum dots as an interface layer: A numerical study

Abstract: Recently, the advantages of perovskite solar cells (PSCs) and a significant increase in power conversion efficiency (PCE) have played an essential role in the preference for these materials. Although different methods are used to increase PCE and reduce losses at the interfaces in PSCs, placing a new layer between the absorber/hole transfer layer (HTL) or between the absorber/electron transfer layer (ETL) stands out as one of the most common methods. In this study, considering stability, sustainability, mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Notably, the inclusion of PQDs significantly enhanced cell efficiency by 30% in formamidinium lead iodide-based structures, illustrating a robust improvement in short circuit current density and overall device performance. Moreover, the study demonstrated the critical role of optimizing resistance parameters (series and shunt resistances) and minimizing defect density within the PQD layer to further augment the PSCs' efficiency [64]. Collectively, this research highlights the revolutionary influence of interface engineering on PSC development, as presented in table 1.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Notably, the inclusion of PQDs significantly enhanced cell efficiency by 30% in formamidinium lead iodide-based structures, illustrating a robust improvement in short circuit current density and overall device performance. Moreover, the study demonstrated the critical role of optimizing resistance parameters (series and shunt resistances) and minimizing defect density within the PQD layer to further augment the PSCs' efficiency [64]. Collectively, this research highlights the revolutionary influence of interface engineering on PSC development, as presented in table 1.…”
Section: Literature Reviewmentioning
confidence: 69%
“…The neutral defect type was chosen and the energy with respect to reference was set to 0.6 eV for the absorber. The energy distribution was selected as single and the carrier capture-cross section was fixed to 1.0×10 -15 cm 2 [21]. Unless otherwise stated, the photodiode simulations were carried out under conditions of 1100 nm incident light, 300 K temperature, and 22.54 W m −2 power density (the maximum power when selecting a single wavelength spectrum in the SCAPS-1D program).…”
Section: Simulation Analysis and Device Structurementioning
confidence: 99%